GROWTH RATE OF Eucalyptus saligna Smith CLONE AFFECTED BY SPACING AND FERTILIZATION - Berger, Rute (2002)
In this research, the spacing (3 x 2, 3 x 3 and 3 x 4 m) and fertilization (400 and 800 kg/ha) effects on growth of Eucalyptus saligna clone were studied. The growth in diameter at breast height (Dbh), height (h) and volume per tree were studied from ages between three and ten years, using the Backman’s function. By covariance analysis it was possible to verify that the treatments with the same spacing showed same growth pattern, for all variables. During all observed period, the fertilization treatment had no effect on mostly of the studied characteristics. The factor spacing had outstanding influence in the growth in diameter and commercial volume without bark per tree. Only the trees under the smallest spacing showed a trend of growing slowly in height over time. The volume yield per ha without bark was smaller for the treatments with larger spacing. No differences in volumetric production were found between the two smaller spacings.